Innovations for community services : 18th International Conference, I4CS 2018, Žilina, Slovakia, June 18-20, 2018, Proceedings /: 18th International Conference, I4CS 2018, Žilina, Slovakia, June 18-20, 2018, Proceedings. (2018) - Unknown
No abstract available